In-silico design and screening of cephalosporin derivatives for their inhibitory potential against Haemophilus influenza (Sciences of Phytochemistry, 2022)
Antibiotics kill bacteria by blocking essential metabolic processes which prevent them from reproducing thereby allowing the immune system to fight bacterial infections. However, the emergence and the quick spread of bacterial resistance against clinically approved antibiotics have become alarming. This necessitates the development of novel treatment options and alternative antimicrobial therapies in the fight against bacterial infections. In this study, we aim to virtually design and carry out in-silico studies to identify a cephalosporin derivative with inhibitory potential against Haemophilus influenza. Data Warrior software, Discovery studio software, PyRx tool, Swiss ADME web tool, and ProTox-II web tool were used to screen the cephalosporin derivatives. Initially, 17 cephalosporin derivatives were preliminarily screened for their toxicity followed by in-silico ADME studies. Among the cephalosporin derivatives, C1, C6, and C12 were found to be the potential drug-like molecules with binding energies of -7.4 kcal/mol, -7.1 kcal/mol, and -7.1 kcal/mol, respectively. In particular, C1 was predicted to have a moderate biological activity with a high bioavailability score. Based on the ADME profile, toxicity, binding energy, drug-likeness, and drug score, we conclude C1 (‘F’ at the 3rd position) as the potential lead molecule to inhibit H. influenza.